(untitled) (Semiárida, 2020)
Nineteen Iines of forage com originated from the crossing among Zea mays x Zea diploperennis in the second year of self-fertilization were evaluated. The analyzed characteristics were: plant height, number of stems per plant ’’. number of ears per plant’, stem diameter and leaf I stem relationship. Rainfall and temperature conditions were optimum during the com cultivation cycle. It was found difference among Iines in all the evaluated characteristics. Lines 3 and 16 exceeded the average for all the forage attributes. Lines 5 and 15 w1thsimilar aptitud do not overcome leaf/stem relationship. The general combinity aptitude will be able to identify the lines with the upper value of digestible dry matter.